Description of a new species of Mediotipula from Albania, with consideration of the eastern Mediterranean as a diversity hotspot (Diptera, Tipulidae) - Keresztes, Lujza (Zookeys, 2018)
Abstract. A new species of the TipulasubgenusMediotipula is described from the south-eastern part of Albania, south-eastern Europe. Morphologically, the new species is most similar to T. (M.) stigmatella Schummel, 1833, but differs mainly with respect to males, having a distinctly shaped posterior margin of tergite 9–10, a widened outer gonostylus and a series of details of the inner gonostylus (anterior end of the anterior arm, shape of the posterior arm), as well as having more bulbous and rounded hypogynal valves in the females. Further morphological differences of the male terminalia between allopatric populations of T. (M.) stigmatella in the Carpathians and Balkans, south-eastern Europe, are discussed.